Youth labour market performance in Spain and its determinants. A micro-level perspective - Dolado, Juan José; Jansen, Marcel; Felgueroso, Florentino; Fuentes, Andrés; Wölfl, Anita (Paris, 2013)
"This paper provides both descriptive and empirical evidence about the main youth labour market problems in Spain. Using the experiences of other EU economies as a benchmark, we document the performance of Spain as regards a wide set of youth labour market dimensions. These include employment and unemployment rates, youth wages, decisions to work and study, youth mobility, type of employment contract, time to find a first job, skill mismatch, etc. Cross-country econometric evidence from different micro-datasets is reported to understand the role played by several underlying supply/demand factors which might explain the difficulties faced by the Spanish youth labour market (www.oecd.org/eco/surveys/Spain)."